2002
DOI: 10.1021/jp020983h
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Effects in the Formation of Molecular Hydrogen on a Graphite Surface via an Eley−Rideal Mechanism

Abstract: The associative desorption of HD (ν,j) and D 2 (ν,j) on a graphite(0001) surface via an Eley-Rideal mechanism has been studied theoretically using a time-dependent wave packet method. We find that product molecules are formed rovibrationally excited and translationally hot. When comparing the different products to earlier calculations on the formation of H 2 on graphite(0001), we find significant isotope effects and possible resonant transitions during the reaction, which might have consequences for the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 81 publications
2
36
0
Order By: Relevance
“…[24], respectively, while the isotope effect on the adsorption of H/D on highly oriented pyrolytic graphite (HOPG) substrate was demonstrated for the first time in laboratory experiments. [25] A combined theoretical and experimental investigation on HD formation on a graphite surface was performed by Zecho et al [26] at T S = 150 K, while a theoretical approach was developed on the same system by Meijer et al [11] at T S = 10 K.…”
Section: Isotope Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[24], respectively, while the isotope effect on the adsorption of H/D on highly oriented pyrolytic graphite (HOPG) substrate was demonstrated for the first time in laboratory experiments. [25] A combined theoretical and experimental investigation on HD formation on a graphite surface was performed by Zecho et al [26] at T S = 150 K, while a theoretical approach was developed on the same system by Meijer et al [11] at T S = 10 K.…”
Section: Isotope Effectmentioning
confidence: 99%
“…[2] Over the last few years, electronic structure calculations as well as the dynamics of H 2 , D 2 , and HD formation after hydrogen atom recombination on graphitic surfaces have been performed by different groups using various approaches. [3][4][5][6][7][8][9][10][11] These studies mainly aim to explain the great abundance of molecular hydrogen observed in the interstellar medium, so the surface temperature (T S ), when explicitly considered in the collisional models, is kept very low, between 10 and 100 K.…”
Section: Introductionmentioning
confidence: 99%
“…has been a subject of ongoing theoretical work over the past decade [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interest in this topic was aroused from the astrophysical issue concerning H 2 formation in the interstellar medium (ISM).…”
Section: Introductionmentioning
confidence: 99%
“…It has been rightly argued that such characteristics are within the accuracy limits of current DFT functionals [6,11,18]. Accordingly, some works take a barrier into consideration with characteristics close to those determined by DFT calculations [9][10][11]15,17] while others consider reaction (1) as being barrier-less [1][2][3][4][5]7,8,[12][13][14][15][16]18] or nearly so [6]. The barrier in the Bachellerie-potential actually increases and moves closer towards the surface when the H b atom is displaced laterally away from the collinear approach (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen adsorption on carbon based materials such as graphite and graphene is relevant to hydrogen storage, 9 band gap engineering, [10][11][12][13] and potentially as the first step in H 2 formation in the interstellar medium. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although there is enormous interest in H adsorption on carbonaceous surfaces, with graphene, graphite and polycyclic aromatic hydrocarbons (PAHs) being the most widely studied model systems, we still don't fully understand the seemingly simple process of how a single H atom adsorbs on the surface.…”
mentioning
confidence: 99%